What, If Anything, Most Memorable Personal Moral Dilemmas Can Tell Us About Women’s and Men’s Moral Competence? - Klimenko, Marina A. (Wydział Filozoficzny, Uniwersytet im. Adama Mickiewicza w Poznaniu, 2021)
Most all popular moral reasoning or moral judgment tests are based on presenting subjects with two or more hypothetical moral dilemmas and asking them to make judgments on the moral quality of arguments supporting and questioning a protagonist’s decision (e.g., the Moral Competence Test by G. Lind). Although these tests have been insightful by tapping some aspect of individuals’ moral-cognitive schemas, moral maturity, or moral development, they also have limitations. Hypothetical moral dilemmas may be too abstract and impersonal, thus failing to create enough emotional salience. Learning more about real-life personally recalled moral dilemmas may reveal more about the individual’s moral mind and experiences. Objective. The current study was conducted to learn more about the personally experienced moral dilemmas, and how they relate to subjects’ level of moral competence and gender. Method. Subjects were asked to recall the most challenging personal moral dilemma; subjects completed the MCT test to measure moral competence. Results. Among some of the findings was that for both, men and women, higher moral competence scores were positively correlated with recalling personal moral dilemmas where the choice had to be made between some altruistic (care for others) and selfish actions. For men, it was the risk of compromising one’s status, whereas for women it was the risk of personal safety.
Keywords: moral competence; moral development; moral dilemmas of college students; sex-differences in moral judgement; MCT